Synergism between recombinant human bone morphogenetic protein 2/absorbable collagen sponge and bone substitutes favors vertical bone augmentation and the resorption rate of the biomaterials: Histomorphometric and 3D microcomputed tomography analysis. Issue 10 (25th March 2020) - Polo, Cristiane Ibanhes; Sendyk, Wilson Roberto; Correa, Luciana; Sendyk, Daniel; Deboni, Maria Cristina Zindel; Naclério‐Homem, Maria da Graça
Abstract: Background: Recombinant human bone morphogenetic protein 2 (rhBMP‐2) is an osteoinductor frequently used for bone regeneration in oral and maxillofacial surgery. There is no consensus about the ideal carrier for this growth factor. The aim of this study was to compare the bone augmentation, bone microarchitecture, and biodegradation rate of additional carriers to rhBMP‐2/absorbable collagen sponge (ACS) in a vertical guided bone regeneration model. Methods: Four titanium cylinders were fixed onto the calvaria of rabbits (n = 20) that received (n = 10) or not (n = 10) rhBMP‐2/ACS in conjunction with one of the carriers: beta‐tricalcium phosphate (β‐TCP), biphasic calcium phosphate (BCP), bovine bone mineral (BBM) or blood clot. The samples were analyzed by means of microcomputed tomography and histomorphology after 14 weeks. Results: All the materials with rhBMP‐2/ACS exhibited improvement on bone augmentation, mainly BCP ( P  = 0.033) and β‐TCP ( P  = 0.038), in the upper portion of the cylinder. Although trabecular anisotropy was improved in all the materials groups, trabecular connectivity was diminished when the biomaterials received rhBMP‐2/ACS. Resorption rate of the remaining biomaterial was improved by rhBMP‐2/ACS, mainly in BBM ( P  <0.01) and β‐TCP ( P  <0.01). BBM exhibited the highest osteoclast density compared with the other materials groups. Conclusions: BCP and β‐TCP biomaterials exhibited a synergic effect with rhBMP‐2/ACS, acting as suitable and viable carriers for vertical bone augmentation. The addition of rhBMP‐2 significantly affected the biodegradation of β‐TCP and BBM, accelerating the resorption of these materials.